Designing self helps groups’s communication strategy to explore women expectation in small enterprises - Sumiati, Sumiati; Rosita, Nadiyah Hirfiyana; Ayuni, Risca Fitri; Attamimi, Dian (MEC-J (Management and Economics Journal), 2019)
Women empowerment is becoming a current issue in sustainable development goals. Every developing country trying to promote the women empowerment issues in every sector. In Indonesia, this issues actively risen by PKK. PKK is the simplest form of self helps group organizations that can be found in almost whole areas of Indonesia. This organization is driven by women members, so they can interact with each other for self-development and group development. In order for these development efforts to be effective, identifying the expectations and needs of the community are very principal before defining the right communication strategy to reach the community. Based on focus group discussion that has been done with PKK members of Desa Jambu as a group of self helps group in developing small and medium enterprises in Desa Jambu, Sumenep there are three expectations related to PKK function that is delivered as learning facilities, cooperation medium, and production unit. To meet those expectations, communication strategy through counseling and training can be chosen as primary strategy.